Integration of geometric deviations of system components with a reduced set of parameters for computed tomography simulations in aRTist - Binder, Felix; Zippert, Patrick; Hausotte, Tino (5th Dimensional X-ray Computed Tomography Conference, 2021)
Radiographic simulation tools like aRTist can be used for parameter studies or optimization of computed tomography (CT) measurements, presumed that the parameters of the simulated CT model represent the CT system. Therefore, various techniques have been developed to adapt simulation model parameters to their real CT system counterparts. However, some parameters are still challenging to adapt, like geometric deviations of CT system components for the duration of a CT scan. In this contribution, a new approach to determine reasonable simulated geometric deviation parameters will be presented, on the assumption that only a reduced set of geometric variation parameters has to be considered. As a baseline, the approach uses an already adapted simulation model without any geometric deviations. Using the distribution of the deviations of a measured surface against an ideal CAD surface as an evaluation criterion, the characteristics of the distribution of the reduced set of geometric variation parameters can be determined iteratively and integrated into to the baseline model. In order to evaluate the approach, different dimensional features are used to compare the refined model and the baseline model to a series of reference CT measurements. This approach can potentially be used towards a full systematic parameter adaption process.<br
Keywords: Computed Tomography; Virtual CT; Simulation Model